2011
DOI: 10.1111/j.1440-1746.2010.06599.x
|View full text |Cite
|
Sign up to set email alerts
|

Asian chronic pancreatitis: The common and the unique

Abstract: Chronic pancreatitis (CP) is a disabling condition worldwide that presents as pain, maldigestion, and diabetes. It is usually perceived as alcohol related, or classified as idiopathic otherwise. However, this is true only for Western countries. Asian CP comprises not only alcohol-related CP but also tropical pancreatitis (TP). Tropical pancreatitis is a unique entity commonly found in South Asia. It shares similar presentations with other CPs for pain and maldigestion. However, its diabetes is more ketosis res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Half of the patients with CP in China, India, and Japan were considered as idiopathic. Tropical pancreatitis is a form of idiopathic CP and affects young adults with the characteristics of diabetes and large calculi . Other toxic causes of CP include cigarette smoke, volatile hydrocarbons, and regular contact with kerosene or paraffin.…”
Section: Chronic Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation
“…Half of the patients with CP in China, India, and Japan were considered as idiopathic. Tropical pancreatitis is a form of idiopathic CP and affects young adults with the characteristics of diabetes and large calculi . Other toxic causes of CP include cigarette smoke, volatile hydrocarbons, and regular contact with kerosene or paraffin.…”
Section: Chronic Pancreatitismentioning
confidence: 99%
“…Tropical pancreatitis is a form of idiopathic CP and affects young adults with the characteristics of diabetes and large calculi. 12 Other toxic causes of CP include cigarette smoke, volatile hydrocarbons, and regular contact with kerosene or paraffin. Smoking is an independent risk factor of CP and smoking increases the risk of CP in a dose-dependent manner.…”
mentioning
confidence: 99%
“…Su prevalencia no está bien definida, hablándose de un 15% de las pancreatitis crónicas en las series médicas y un 26% de los procesos pancreáticos benignos en las series quirúrgicas 2 . Su distribución geográfica es mundial, aunque es más frecuente en los países asiáticos 3 .…”
Section: Introductionunclassified
“…6 In more than half of AIP patients, anticarbonic anhydrase II and anti-lactoferrin levels may be elevated. 12 An autoimmune pathogenesis has been proposed because the condition is occasionally associated with autoantibodies or other autoimmune-associated diseases. 6 Zamboni et al have reported Sjögren's syndrome being the most frequent autoimmune disease in patients with AIP.…”
Section: Figu Rementioning
confidence: 99%